Evolução cromossômica, diversidade genética e história demográfica em espécies do gênero Pyrrhulina (Characiformes, Lebiasinidae) - Moraes, Renata Luiza Rosa de (2024)
The Lebiasinidae family includes seven genera of tiny freshwater fishes that live in streams throughout Central and South America (except Chile). The family's representatives have a wide range of shapes and colors, making them highly desirable in the aquarium industry. Despite being a group that stands out within the Characiform order for its diversity of species, this family has received little attention, owing to collection challenges, chromosome obtaining, and complex taxonomy. Although they constitute a substantial challenge, multiple cytogenetic and molecular research involving the group have been developed throughout the years, contributing considerably to the beginning of the resolution of various uncertainties. Thus, our study is part of a larger cytogenetic and genomic effort to understand the evolutionary history of the Lebiasinidae family. Continuing the studies, with a primary focus on the genus Pyrrhulina, cytogenetic, molecular, and genetic analyses were combined with the goal of analyzing the group's karyotypic evolution, understanding the influence of the sex chromosome system in Pyrrhulina species differentiation, and organizing a phylogeny based on molecular data from the Lebiasinidae family. Five new Pyrrhulina species (Pyrrhulina aff. marilynae, Pyrrhulina cf. laeta, Pyrrhulina marilynae, Pyrrhulina obermulleri and Pyrrhulina sp.) were studied using conventional and molecular cytogenetic techniques, including Giemsa, C-banding, repetitive DNA mapping, comparative genomic hybridization (CGH), and whole chromosome painting (WCP). The results showed a conserved 2n for most species, ranging from 40 to 42 chromosomes and a predominantly acrocentric karyotype, with P. marilynae being an exception, with 2n=32 and the unusual presence of four pairs of metacentric chromosomes, the plesiomorphic status of which is questioned. The distribution of microsatellites is similar among species, while the number and position of rDNA sites vary greatly. Interspe-cific CGH tests revealed moderate divergences in repetitive DNA content between the species' genomes. Surprisingly, the WCP studies supported the theory that Pyrrhulina semifasciata's X1X2Y multiple sex chromosome system evolved. To better understand the formation of such a sex chromosome system and the karyotypic reduction observed in P. marilynae, analyses were also carried out using satellite DNA sequences from these species. The results showed the possible influence of these sequences on the karyotype reduction of P. marilynae and reinforced the hypothesis about the formation of the sex chromosome system of P. semifasciata. Furthermore, to conclude the studies conducted here, the first karyotype of Copella was described, along with a phylogeny based on molecular data of representatives from each of the genera of Lebiasinidae, which contributed to discussions about the family's internal phylogenetic relationships. In conclusion, the data point to the possibility that structural rearrangements combined with a high dynamic of repetitive DNAs drove the karyotypic differentiations under study, particularly in the case of the genus Pyrrhulina.